2016
DOI: 10.5539/ijsp.v5n3p42
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Examination of Bank Crashes Using Panel Logistic Regression: Turkish Banks Failure Case

Abstract: Crises in the financial sector over the last two decades have shown the importance of early warning systems, especially for bank failures. This study aims to develop an early warning system for Turkish commercial bank failures using panel data from 2002 to 2012. The data was analyzed using pooled logistic regression versus random panel logistic regression. The dependent variable was the bank failure, defined as the return-on assets ratio. Factor analysis was used to construct independent variables of financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Therefore, a logit regression model estimation method was used, which assumes that the error term is a linear probability model of a logistic distribution rather than a normal distribution (Khan & Shaw, 2011). Compared to the cross‐sectional logit regression model, the panel logit regression model can resolve the retro‐causality issue because it can control for the unobserved characteristics of the study subject, using various medical expenses as an independent variable and the debt burden appearing between T‐1 and T as a dependent variable (Erdogan, 2016). Fixed‐effect panel models and random‐effect panel models exist—unlike the former, the latter obtains estimates ​​of stable characteristics (Larsen & Merlo, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a logit regression model estimation method was used, which assumes that the error term is a linear probability model of a logistic distribution rather than a normal distribution (Khan & Shaw, 2011). Compared to the cross‐sectional logit regression model, the panel logit regression model can resolve the retro‐causality issue because it can control for the unobserved characteristics of the study subject, using various medical expenses as an independent variable and the debt burden appearing between T‐1 and T as a dependent variable (Erdogan, 2016). Fixed‐effect panel models and random‐effect panel models exist—unlike the former, the latter obtains estimates ​​of stable characteristics (Larsen & Merlo, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The study showed that bank profitability per employee, ability of bank to repay its debt, leverage ratio and the banking operations has a negative impact on the bank`s failure. Erdogan (2016) attempted to develop an early warning system for the banking sector in Turkey using panel data during the period 2002 to 2012. The study used random panel logistic regression versus pooled logistic regression.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in Pakistan, adopting the e-banking service had a significant positive impact on ROE which meant the adoption of e-banking reduced the cost of bank operations and increased customer satisfaction and bank profitability (Rauf & Ismatullaevich, 2013). Erdogan (2016) presented panel logistic regression models containing different financial ratios (e.g. loan due ratio and cost to income ratio) to…”
Section: Bank Performancementioning
confidence: 99%
“…Therefore, banks can compare their current and historical performance in investments and earnings (MacDonld & Koch, 2006). Similar to Bailey et al (2011), Erdogan (2016) and Rauf & Ismatullaevich (2013), this research uses both ROA and ROE as dependent variables.…”
Section: = ≤ 15%mentioning
confidence: 99%